The Cooperative Care Model: an innovative approach to deliver blood and marrow stem cell transplant care. - Schmit-Pokorny K; Franco T; Frappier B; Vyhlidal RC (Clinical Journal of Oncology Nursing)
Competition among healthcare institutions, the need to improve outcomes, and the desire to decrease costs have motivated blood and marrow stem cell transplant centers to develop innovative care models. In an effort to meet these challenges, a major midwestern medical center adapted the transplant process to the outpatient setting. This transition created greater educational and care demands for patients and families. To address these demands and provide improved accommodations and amenities for patients and families, the center adopted an innovative model of care, Cooperative Care, for transplant recipients. Cooperative Care embraces patients and families as key members of the healthcare team. A family member serves as a primary caregiver for the patient during the acute inpatient phase of the transplant. Care becomes more personal and individualized, cost is reduced, the rate of rehospitalization potentially is decreased, and patients ultimately become more confident and competent in caring for themselves. The healthcare team shifted its care philosophy to incorporate a care partner, increase patient control and independence, and create greater emphasis on education. Outcomes, including patient satisfaction, have demonstrated success and motivated expansion of this model to other patient populations.